You are on page 1of 13

1 Sequences

Definition of Terms
Definition. A sequence is a function f whose domain is the set of natural numbers N (or a finite
subset of N), that is,

f :N R
1 7 a1
2 7 a2
3 7 a3
..
.
n 7 an

1. The elements of the function are called the terms of the sequence.

2. We denote the nth term of the sequence by an .

3. We denote the sequence by {a1 , a2 , a3 , . . .} or {an }


n=1 or simply {an }.

4. If the domain is a finite subset of N, then it is called a finite sequence.

5. If the domain is N, then it is called an infinite sequence.

Definition. A sequence is defined recursively if the nth term arises from a formula that depends
on the previous terms of the sequence.
1 1 1 1 2 1 4 5 1 1
Examples: 1(a). 1, , , , ; 1(e). 1, , , ; 1(i). 1, 1, 2, 3, 5; 1(k). 1, , 1, , 1
2 3 4 5 3 3 27 81 2 3
Remarks:

1. Two sequences {an } and {bn } are equal if an = bn for all n.

2. To get a visual representation of the terms of the sequence {an }, we can do either of the
following:

(a) Plot the points corresponding to successive elements of the sequence on the number line.
(b) Plot the points (n, an ) on the Cartesian plane.

Example: 1(a). draw plot on the real number line and on the Cartesian plane

Convergence of Sequences
Definition. The limit of a sequence {an } (denoted by lim an ) is equal to L if we can make an
n
as close as we want to L by taking n sufficiently large. In this case, the sequence is said to be
convergent. Otherwise, the sequence is said to be divergent.

Theorem. If f is a function that is continuous on [1, ) such that f (n) = an for all n N, then

lim an = lim f (x).


n x

Remark: Limit theorems for functions can also be applied to limits of sequences.

Theorem. (Squeeze Theorem) Let {an }, {bn } and {cn } be sequences such that an bn cn for
all values of n beyond some index N . If the sequences {an } and {cn } have a common limit L as
n , then {bn } also has the limit L as n .

Examples: 3(a). 0 if r > 0; 3(b). no limit; 3(c). 1; 3(e). 0; 3(h). 0; 3(k). 0 (use Squeeze
Theorem, an = 0 and cn = 1/n); 4. |r| < 1

Definition. A sequence {an } is said to be

1
1. increasing if an+1 an (or (an+1 an ) 0) for all n,

2. decreasing if an+1 an (or (an+1 an ) 0) for all n,

3. monotone if it is either increasing or decreasing.

Examples: 5(a). increasing; 5(b). decreasing; 5(d). neither

Definition. A real number R is said to be

1. an upper bound of {an } if an R for all n,

2. a lower bound of {an } if an R for all n,

3. the least upper bound of {an } if it is the smallest upper bound of {an }, that is, R r for any
upper bound r of {an },

4. the greatest lower bound of {an } if it is the largest lower bound of {an }, that is, R r for any
lower bound r of {an }.

Definition. A sequence {an } is said to be

1. bounded above if it has an upper bound,

2. bounded below if it has a lower bound,

3. bounded if it is bounded above and below.

Examples: 6(a). bounded below; 6(b). bounded above; 6(c). bounded; 6(d). neither; 6(e).
bounded
Remarks:

1. An increasing sequence is bounded below by a1 , and a decreasing sequence is bounded above


by a1 .

2. Not all bounded sequences are convergent.

3. Not all monotone sequences are convergent.

Theorem. (Bounded Monotone Convergence Theorem) Every bounded monotone sequence is con-
vergent.

Examples: 7(a). convergent; 7(c). divergent; 7(g). divergent; 7(k). divergent; 7(l). convergent
by BMCT; 7(p). convergent by BMCT (limit is 6)
Remark: To test for convergence of sequences, we use one of the following methods:

1. Look at limit of f (x), where f (n) = an .

2. Use BMCT.

3. Use the Squeeze Theorem.

Homework
I, 3(j), 7(f), 7(q).

2
2 Series of Constant Terms
Definition. An infinite series is an expression of the form

X
an = a1 + a2 + a3 + . . . + an + . . . .
n=1

1. The numbers a1 , a2 , . . . , an , . . . are called terms of the series.



X
2. Let Sn denote the sum of the first n terms of the series an , that is,
n=1

S1 = a1
S2 = a1 + a2
S3 = a1 + a2 + a3
..
.
Sn = a1 + a2 + . . . + an

We call Sn the nth partial sum of the series and {Sn } the sequence of partial sums.

X
Definition. Let {Sn } be the sequence of partial sums of the series an = a1 + a2 + a3 + . . .. If
n=1

X
{Sn } converges to a limit S, then we say that an is a convergent series and its sum is equal to
n=1
S, that is,

X
an = lim Sn = S.
n
n=1

X
On the other hand, if {Sn } is a divergent sequence, then the series an is said to be a divergent
n=1
series. A divergent series has no sum.
n(n + 1) 1 n+2
Examples: 1(a). ; 1(c). 1 if n is odd, 0 if n is even; 1(e). 1 ; 4. S2n >
2 n+1 2

X
Theorem. The geometric series arn1 = a +ar +ar2 +. . ., where a and r are nonzero constants
n=1
is

X a
1. convergent if |r| < 1 and arn1 = .
n=1
1r

2. divergent if |r| 1.

X
Proof. If r = 1, then the geometric series becomes a. So, Sn = na and
n=1
(
+, a>0
lim Sn = lim na =
n n , a<0

hence, the series is divergent.


For r 6= 1, the nth partial sum is Sn = a + ar + ar2 + ar3 + . . . + arn1 . Multiplying the equation
by the common ratio r, we get

rSn = ar + ar2 + ar3 + . . . + arn .

3
Therefore,

Sn rSn = a + ar + ar2 + ar3 + . . . + arn1 ar + ar2 + ar3 + . . . + arn
= a arn
(1 r)Sn = a (1 rn )
a (1 rn )
Sn =
1r
Taking the limit of the sequence of partial sums, we have
a
lim Sn = , |r| < 1.
n 1r
If |r| 1, the limit does not exist.

Examples: 2(a). convergent, sum is 3; 2(b). convergent, sum is 18/5; 2(c). divergent; 2(d).
1
convergent if |x| < 1, sum is , divergent otherwise; 3(a). 1147/495
1x
Remarks:

X
X
X
X
1. If an and bn are convergent, then (an bn ) is convergent and (an bn ) =
n=1 n=1 n=1 n=1

X
X
an bn .
n=1 n=1

X
X
X
2. If c is a nonzero constant and an is convergent, then can is also convergent and can =
n=1 n=1 n=1

X
c an .
n=1

X
X
3. If c is a nonzero constant and an is divergent, then can is also divergent.
n=1 n=1

4. Convergence is unaffected by deleting a finite number of terms from a series; that is, for any

X
X
positive integer k, an = a1 + a2 + a3 + . . . and an = ak + ak+1 + ak+2 + . . . are both
n=1 n=k
convergent or both divergent.

X
Theorem. If an is convergent, then lim an = 0.
n
n=1

X
Proof. First, note that for any given series an ,
n=1

an = (a1 + a2 + . . . + an1 + an ) (a1 + a2 + . . . + an1 )


= Sn Sn1 ,

where Sn denotes the nth partial sum of the series.



X
Suppose now that an is convergent. Then by definition, there is a number S such that
n1
lim Sn = S. Therefore,
n

lim an = lim (Sn Sn1 )


n n
= lim Sn lim Sn1
n n
= S S = 0.

4
Remark: The previous statement is not useful to determine convergence of a series. However, its
contrapositive is useful to check for divergence of a series.

X
Theorem. (Divergence Test) If lim an 6= 0, then the series an is divergent.
n
n=1

Examples: 2(i). divergent by Divergence Test; 2(k). divergent by Divergence Test; 2(l).
X
1
convergent, sum is 4; 2(n). divergent since is 4 times the harmonic series
n=1
4n

3 Convergence Tests for Series with Nonnegative Terms


Sometimes, it is difficult to find an expression for the nth partial sum of the series. This makes it
difficult to determine whether the series is convergent or divergent. However, there are other tests
to determine the convergence of a series.
The following tests can be used if the terms of the series are nonnegative.

X
Theorem. (Integral Test) Let an be a series with nonnegative terms. Suppose f is continuous,
n=1
positive, and decreasing in [1, ) and f (n) = an for all n N.
Z

1. If the improper integral f (x) dx converges, then the series converges.


1
Z

2. If the improper integral f (x) dx diverges, then the series diverges.


1

Remarks:

1. Because convergence is not affected by the first few terms of the series, the integral and the
series need not start at n = 1. We can relax the condition on f : Suppose f is continuous,
positive, and decreasing in [N, ), where N N.
Z
X
2. The sum of the series is not equal to the integral: an 6= f (x) dx.
n=1 1

Examples: 1(i). convergent; 2. convergent when p > 1; 1(b). convergent (sum is 2 /6); 1(e).
divergent; 1(f). divergent; 1(h). convergent; 1(j). divergent

X
X
Theorem. (Comparison Test) Suppose an and bn are series with nonnegative terms.
n=1 n=1

X
X
1. If an bn for all n and bn is convergent, then an is also convergent.
n=1 n=1

X
X
2. If an bn for all n and bn is divergent, then an is also divergent.
n=1 n=1

X
X
1 1
Examples: 1(a). convergent, compare with n1
; 1(m). convergent, compare with ;
n=1
2 n=1
2n

X
X
1 1
1(o). convergent, compare with ; 1(f). divergent, compare with
n=1
n2 n=1
n
Remarks:

1. Compare with series whose convergence (or divergence) is known.

2. Application is limited because of the conditions of the comparison test; ex. 1(q).

X
X
Theorem. (Limit Comparison Test) Suppose that an and bn are series with positive terms.
n=1 n=1

5
an
1. If lim = c > 0, then either both series converge or both series diverge.
n bn

X
X
an
2. If lim = 0 and bn converges, then an also converges.
n bn
n=1 n=1

X
X
an
3. If lim = + and bn diverges, then an also diverges.
n bn
n=1 n=1

Remarks:

X
an
1. No conclusion when lim = 0 and bn diverges.
n bn
n=1

X
an
2. No conclusion when lim = and bn converges.
n bn
n=1

X
X
1 1
Examples: 1(q). convergent, compare with ; 1(r). convergent, compare with ;
n=1
2n n=1
3n

X 1
1(s). convergent, compare with ; 1(x). convergent, discard the first 3 terms and compare
n=1
n3

X 1 X (n + 3)3
and
n=1
n! n=1
(n + 3)!
Remarks:

1. Adding or subtracting a finite number of terms will not change the convergence or divergence
of a series.

2. If all of the terms of a series are positive, regrouping the terms will not affect the convergence
X
1
of the series; ex. n
.
n=1
2

3. If all the terms are positive, rearranging the terms will not affect the convergence of the series;
X
1
ex. .
n=1
2n

4. If there are both positive and negative terms on the series, the previous remarks cannot be

X
applied; ex. (1)n .
n=1

X
Theorem. If an is a given convergent series of positive terms, its terms can be grouped in any
n=1
manner and the resulting series also will be convergent and will have the same sum as the given
series.

4 Convergence Tests for Series with Positive and Negative Terms


The following convergence tests can be applied to series with both positive and negative terms.

Definition. An alternating series is a series whose terms are alternately positive and negative. It
is of the form
X X
(1)n bn or (1)n1 bn ,
n=1 n=1

where bn > 0 for all n.

Theorem. (Alternating Series Test) If a given alternating series satisfies

1. lim bn = 0, and
n

6
2. the sequence {bn } is decreasing, i.e., bn+1 bn for all n,

then the series is convergent.

[ insert diagram of number line here ]


Examples: 1. convergent; 9. divergent; 2. convergent

X
X
Definition. A series an is said to be absolutely convergent if the series of absolute values |an |
n=1 n=1

X
X
X
is convergent. If an is convergent but |an | is divergent, then an is said to be conditionally
n=1 n=1 n=1
convergent.

Examples: 1. conditionally convergent; 4. absolutely convergent



X
Theorem. If an is absolutely convergent, then it is convergent.
n=1

X
X
Proof. Suppose that an is absolutely convergent. Then by definition, |an | is convergent.
n=1 n=1
Note that for all n,
|an | an |an |,
which implies
0 an + |an | 2|an |

X
X
X
Since |an | is convergent, then so is 2|an |. By the Comparison Test, (an + |an |) is also
n=1 n=1 n=1
convergent.
Now,

X
X
an = (an + |an | |an |)
n=1 n=1
X
X
= (an + |an |) |an |.
n=1 n=1


X
Both series on the right-hand side of the equation are convergent. Therefore, an is also conver-
n=1
gent.

Example: 5. convergent since it is absolutely convergent


Remarks:

1. The sum of a conditionally convergent series is different when the terms of the series are
rearranged, ex.

X (1)n1 1 1 1 1 1 1 1 1 1 1 1
= 1 + + + + + +
n=1
n 2 3 4 5 6 7 8 9 10 11 12

1 1 1 1 1 1 1 1
= 1 + + +
2 4 3 6 8 5 10 12
1 1 1 1 1 1
= + + +
2 4 6 8 10 12
1 1 1 1 1 1
= 1 + + +
2 2 3 4 5 6
1
S 6= S
2

2. The sum of an absolutely convergent series is fixed even if the terms of the series are rearranged.

7
3. There are two tests to determine whether a series is absolutely convergent: the Ratio Test and
the Root Test.

X
Theorem. (Ratio Test) Suppose that an is a series with nonzero terms.
n=1

an+1
1. If lim = L < 1, then the series is absolutely convergent, and is therefore convergent.
n an

an+1 an+1
2. If lim lim = , then the series is divergent.
n = L > 1 or n
an an

an+1
3. No conclusion can be made regarding convergence of the series if lim
= 1.
n
an
Examples: 15. absolutely convergent, hence convergent; 17. divergent; 19. absolutely conver-
gent, hence convergent; 21. divergent

X
Theorem. (Root Test) Given a series an .
n=1

1. If lim |an |1/n = L < 1, then the series is absolutely convergent, and is therefore convergent.
n

2. If lim |an |1/n = L > 1 or lim |an |1/n = , then the series is divergent.
n n

3. No conclusion can be made regarding the convergence of the series if lim |an |1/n = 1.
n

Examples: 22. absolutely convergent, hence convergent; 24. absolutely convergent, hence
convergent; 26. divergent; 27. absolutely convergent, hence convergent

Summary for Tests for Convergence


1. Divergence Test

X 1
2. Special types: geometric, p-series, , alternating
n=1
n!

3. Comparison Test or Limit Comparison Test (series of positive terms)

4. Integral Test (series of positive terms)

5. Test for absolute convergence (series of positive and negative terms)

6. Ratio Test: factorials, rational, k n

7. Root Test: (bn )n

8
5 Power Series
We are now going to consider series whose terms are polynomials in x. By substituting a real number
for x, we arrive at a series with constant terms. Our goal is to find all the possible values of x that
will make the resulting series convergent.

Definition of Terms

X
Definition. A series of the form cn (x a)n = c0 + c1 (x a) + c2 (x a)2 + c3 (x a)3 + . . .,
n=0
where x is a variable, a is a fixed real number and the cn s are constants, is called a power series
centered at a or a power series about a. Note that in the definition, we adopt the convention that
(x a)0 = 1 even when x = a.

X X xn X (x + 1)n
Examples: xn (centered at x = 0); (centered at x = 0); (centered at
n=0 n=0
n! n=1
n
x = 1)
Remark: We can also have a power series in (x), where (x) is a real-valued function. This power
series can be expressed as

X
cn ((x))n = c0 + c1 (x) + c2 ((x))2 + c3 ((x))3 + . . . .
n=0

However, this is rarely used in practical applications. We will only focus on power series centered
at a.

X
Theorem. If the power series cn (x a)n is convergent for x = x1 (where x1 6= a), then it is
n=0
absolutely convergent for all values of x for which |x a| < |x1 a|.

X
Theorem. If the power series cn (x a)n is divergent for x = x1 (where x1 6= a), then it is
n=0
divergent for all values of x for which |x a| > |x1 a|.

X
Theorem. For a given power series cn (x a)n , there are only three possibilities:
n=0

1. The series converges only at x = a.

2. The series converges for all real values of x.

3. There is a positive number R such that the series converges if |x a| < R and diverges if
|x a| > R.

X
Definition. Given a power series cn (x a)n .
n=0

1. The number R in the previous theorem is called the radius of convergence of the power series.
By convention, R = 0 if the series converges at only one point and R = if the series
converges for all real values.

2. The interval of convergence is the set of all values of x so that the series converges. In the
case where R = 0, the interval of convergence is {a}. In the case where R = , the interval
of convergence is R.

Remarks:

1. In the case where R > 0, there are four possibilities for the interval of convergence:

(a R, a + R) [a R, a + R) (a R, a + R] (a R, a + R)

9
2. Most of the time, the radius and interval of convergence can be obtained using the Ratio Test
or the Root Test.

3. For the endpoints of the interval, the series may be absolutely convergent, conditionally con-
vergent, or divergent. The Ratio Test or the Root Test will fail, so other convergence tests
should be use to check for convergence of the series.

Examples: 1(a). R = 1, (1, 1); 1(c). R = , R; 1(d). R = 0, {0}; 1(b). R = 32 , 32 , 32 ;
1(l). R = 1, [2, 0); 1(m). R = 1, (1, 3); 1(p). R = 2, [1, 3]

Power Series Representations of Functions



X
The sum of a power series cn (x a)n is a function
n=0


X
f (x) = cn (x a)n = c0 + c1 (x a) + c2 (x a)2 + c3 (x a)3 + . . . ,
n=0

whose domain is the interval of convergence of the power series. Our goal is to represent certain
types of functions as sums by manipulating a geometric series or by differentiating or integrating
such a series.
We start with the power series

X
xn = 1 + x + x2 + x3 + . . . ,
n=0

which is a geometric series with a = 1 and common ratio r = x. This is convergent whenever |x| < 1
and divergent when |x| 1. Using the formula for the sum of a convergent geometric series,

X
1
= xn , |x| < 1.
1 x n=0

Examples: 2. the graphs are close to each other when |x| < 1, otherwise the graphs are

X X X (1)n xn
very different; 3(a). (1)n xn , |x| < 1; 3(b). x2n , |x| < 1; 3(d). , |x| < 3; 3(e).
n=0 n=0 n=0
3n+1

X (1)n xn+2
, |x| < 3
n=0
3n+1

Remark: Power series are used to calculate function values like sin x, ex , ln x and x, which cannot
be evaluated by the usual arithmetic operations.

Differentiation and Integration of Power Series



X
Theorem. If the power series cn (x a)n has radius of convergence R > 0, then the function f
n=0
defined by

X
f (x) = cn (x a)n = c0 + c1 (x a) + c2 (x a)2 + c3 (x a)3 + . . .
n=0

is differentiable (and therefore continuous) on the interval (a R, a + R) and



X
1. f 0 (x) = c1 + 2c2 (x a) + 3c3 (x a)2 + 4c4 (x a)3 + . . . = ncn (x a)n1
n=1
Z
(x a)2 (x a)3 X (x a)n+1
2. f (x) dx = C + c0 (x a) + c1 + c2 + = C + cn .
2 3 n=0
n+1

The radii of convergence of the following power series are both R.

10
Remark: The radius of convergence is the same, but the interval of convergence may change.

X xn X
Examples: 4(a). f 0 (x) = , domain [1, 1); 3(f). nxn1 , domain (1, 1); 3(f).
n=0
n + 1 n=1

X n 1
X
2n2
X (1)n1 xn
Use the item to find (substitute x = 2 ); 3(h). nx , |x| < 1; 3(l). ln 3+ ,
n=1
2n n=1 n=1
n3n

X 1
|x| < 3; 3(l). Use the item to find n
(substitute x = 1); 5. Show that f 0 (x) = f (x) and
n=1
n3
X n
x
f (0) = 1; 3(i). (1)n . 6. Compute up to second derivative and plug in to differential equation;
n=0
n!
n 2n+1
X (1) x X (1)n x2n+1
3(p). ; 3(n).
n=0
n!(2n + 1) n=0
2n + 1

Products and Quotients of Power Series


Finding the products and quotients of power series is similar to finding the product and quotient
of polynomials. However, it is important that the two series are absolutely convergent so that the
product or quotient can be computed. Recall that only absolutely convergent series can have the
terms be regrouped or rearranged and still arrive at the same sum.
2 4 31 x3 2x5
Examples: ex tan1 x = x x3 + x5 + ; tan x = x + + +
3 30 3 15

6 Taylor and Maclaurin Series


In the previous section, we were able to find a power series representation for certain functions. In
general, if a function has a power series representation, there is a method to find it.
Suppose f is a function that can be represented by a power series about x = a:

f (x) = c0 + c1 (x a) + c2 (x a)2 + c3 (x a)3 + c4 (x a)4 + c5 (x a)5 + . . . , |x a| < R.

If we differentiate f repeatedly, then for |x a| < R we get

f 0 (x) = c1 + 2c2 (x a) + 3c3 (x a)2 + 4c4 (x a)3 + 5c5 (x a)4 + . . .


f 00 (x) = 1 2c2 + 2 3c3 (x a) + 3 4c4 (x a)2 + 4 5c5 (x a)3 + . . .
f 000 (x) = 1 2 3c3 + 2 3 4c4 (x a) + 3 4 5c5 (x a)2 + . . .
..
.

If we let x = a, then

f (a) = c0
f 0 (a) = c1
f 00 (a) = 2c2
f 000 (a) = 2 3c3
f (4) (a) = 2 3 4c4
..
.

If we continue this process, we get the generalization

f (n) (a) = 2 3 4 . . . ncn = n!cn .

Solving for the nth coefficient, we obtain


f (n) (a)
cn = .
n!

11
Theorem. If f has a power series representation about a, that is if

X
f (x) = cn (x a)n , |x a| < R
n=0

f (n) (a)
then its coefficients are given by the formula cn = .
n!
Definition. Given a real-valued function f (x).
1. The power series

X f (n) (a) f 0 (a) f 00 (a) f 000 (a)
(x a)n = f (a) + (x a) + (x a)2 + (x a)3 +
n=0
n! 1! 2! 3!

is called the Taylor series of f about a.


2. The power series

X f (n) (0) n f 0 (0) f 00 (0) 2 f 000 (0) 3
x = f (0) + x+ x + x +
n=0
n! 1! 2! 3!

is called the Maclaurin series of f .



X xn X x2n+1 X x2n X x2n+1
Examples: 1(a). ; 1(b). (1)n ; 1(c). (1)n ; 1(d). (1)n ;
n=0
n! n=0
(2n + 1)! n=0
(2n)! n=0
(2n)!

2
X (x 2)n X (1)n 3 2n X (1)n 2n+1 X
2(a). e ; 2(c). x + x ; 2(f). (1)n (x
n=0
n! n=0
2(2n)! 3 n=0
2(2n + 1)! 3 n=0
1)n ; 3(a). e2 1
Remark: The Taylor/Maclaurin series of f is not necessarily equal to f .
Example: 4. Maclaurin series expansion is 0 (use LHopitals Rule), but f (x) 6= 0 if x 6= 0
Theorem. Let f be a function such that f and its derivatives exist in some interval (a r, a + r).
Then the function is represented by its Taylor series if and only if
f (n+1) (zn )
lim Rn (x) = lim (x a)n+1 = 0,
n n (n + 1)!

where zn is some number between x and a.

7 Binomial Series
Recall that if k is a natural number, the binomial series expansion of (a + b)k is given by
k(k 1) k2 2 k(k 1) . . . (k n + 1) kn n
(a + b)k = ak + kak1 b + a b ++ a b + + kabk1 + bk .
2! n!
Note that

k
= 1,
0

k k(k 1)(k 2) . . . (k n + 1)
= ,
n n!
and so
k
X
k k
(a + b) = akn bn .
n=0
n
In particular, we have
k
X k
k
(1 + x) = xn .
n=0
n
We now generalize the binomial series to the case where k is any real number.

12
Theorem. (The Binomial Theorem) Let k be a real number and |x| < 1.

k(k 1) 2 k(k 1)(k 2) 3 k(k 1) . . . (k n + 1) n


(1 + x)k = 1 + kx + x + x + + x +
2! 3! n!
X
k(k 1) . . . (k n + 1) n
= 1+ x
n=1
n!

If k is a positive integer, the binomial series terminates after a finite number of terms.

Proof. For |x| < 1, let



X k(k 1) . . . (k n + 1) n
f (x) = 1 + x .
n=1
n!
Then
X k(k 1) . . . (k n + 1) n1
f 0 (x) = x .
n=1
(n 1)!
Multiplying f 0 (x) by x,

X k(k 1) . . . (k n + 1) n
xf 0 (x) = x
n=1
(n 1)!

X k(k 1) . . . (k n + 1) n
= n x .
n=1
n!

Rewriting f 0 (x),

X
0 k(k 1) . . . (k n + 1) n1
f (x) = k + x
n=2
(n 1)!

X k(k 1) . . . (k n + 1) n
= k+ (k n) x .
n=1
n!

The series representations for f 0 (x) and xf 0 (x) are absolutely convergent for |x| < 1, so the sum of
the two series is given by
!

X
k(k 1) . . . (k n + 1) n
(1 + x)f 0 (x) = k 1 + x
n=1
n!
= kf (x).

Therefore,

f 0 (x) k
=
f (x) 1+x
d d
(ln f (x)) = ln(1 + x)k
dx dx
ln f (x) = ln(1 + x)k + C

But f (0) = 1, so C = 0. Therefore, f (x) = (1 + x)k



X
X
1 3 5 . . . (2n 1) n 1 3 . . . (2n 1) 2n
Examples: 1(a). 1+ (1)n n
x , |x| < 1; 1(b). 1+ x ,
n=1
2 n! n=1
2n n!

X 1 3 . . . (2n 1) x2n+1 X
|x| < 1; 1(c). x + n n!
, |x| < 1; 1(e). (1)n (n + 1)xn , |x| < 1
n=1
2 2n + 1 n=0

13